Implementasi Market Basket Analysis Dengan Algoritma Frequent Pattern Growth Pada Data Transaksional di Electronic Commerce - Fairuzindah, Athaya; Islami, Istiqomah Rabithah Alam; Rexa, Nafa; Anggraini, Silvia; Sunandi, Etis (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Growth of the e-commerce industry has resulted in a massive volume of transaction data, necessitating effective data analysis techniques to extract customer purchasing patterns. The Frequent Pattern Growth (FP-Growth) algorithm is one of the data mining methods that can be used to identify frequently occurring purchase patterns without explicitly generating candidate itemsets. This study aims to implement and evaluate the performance of the FP-Growth algorithm in analyzing e-commerce transaction data to identify recurring shopping patterns. The research methodology includes transaction data collection, data preprocessing, FP-Growth algorithm implementation, and result analysis. This study utilizes an e-commerce transaction dataset from an online retail store based in the United Kingdom, comprising 541,909 transaction records. The research findings indicate that the FP-Growth algorithm is efficient in identifying frequently occurring transaction patterns. Using a support threshold of 1% and a confidence level of 80%, 13 association rules were discovered, demonstrating relationships between frequently co-purchased products. Further analysis shows that these findings can be leveraged by e-commerce businesses to develop marketing strategies based on product recommendations. In conclusion, the FP-Growth algorithm is an effective approach for extracting purchasing patterns from large-scale e-commerce transaction data.